CRIMINALITY DATA SCRUTINY USING LOGISTIC REGRESSION ALGORITHM - Sekhar, G. Soma; Abhinaya, Puvvada; Jayani, Rachapudi; Rao, Dr. D. Srinivasa (International Journal of Research -GRANTHAALAYAH, 2023)
The quantity of criminal cases in India is rising rapidly, which is the reason there are likewise a rising number of cases as yet extraordinary. Criminal cases are expanding ceaselessly, making it difficult to sort and determine them. It's essential to perceive an area's patterns of crime to prevent it from working out. On the off chance that the specialists entrusted with researching violations have a strong comprehension of the patterns in crime happening in a specific area, they will actually want to improve. Finding the examples of crime in a particular area should be possible by applying AI and different calculations. This review predicts the sorts of wrongdoings that will happen in a given area utilizing wrongdoing information, which facilitates the characterization of criminal cases and considers suitable activity. This exploration utilizes information from the most recent 18 years that were assembled from various solid sources. This article utilized choice, erasing invalid qualities, and mark encoding to clean and support the information since information pre-handling is similarly just about as vital as definite expectation. A compelling AI model for estimating the resulting criminal case is given by this exploration.